Public beliefs on the relationship between lying and memory - Riesthuis, Paul (Psychology, crime & law, 2022)
In two studies, we surveyed the beliefs of undergraduate students (Study 1) and the general public (Study 2) about deceptive behavior, memory functioning, and the effects of lying on memory. We compared participants’ beliefs with the current memory and deception literature. Overall, participants in both studies believed that different types of lies (i.e. false denials, feigning amnesia, fabrication) would elicit different memory impairing effects, although they did not know what specific kind of memory impairment (e.g. forgetting, false memory). In line with previous experimental studies, participants experienced difficulties in retrieving memories after falsely denying or feigning amnesia. Moreover, participants believed that lying would impact other people’s memory such as that people would start to believe in their own lies. Meanwhile, they also indicated that these effects would be minimal for themselves. Interestingly, our results showed that false denials are used quite frequently in daily life. Finally, we found that undergraduate students’ beliefs about memory were in line with scientific evidence, while the general public continues to have erroneous beliefs about memory. When the general public plays a role in the courtroom (e.g. jury members), we recommend involving memory experts in the assessment of reliability of statements when lying was involved.